The Influence of Harvesting Period on Lipid Associated Antioxidant Activity of Semicontinuously Grown Chlorella vulgaris - Chrismadha, Tjandra; Sartika, Diani; Setyaningsih, Iriani; Uju, Uju (Annales Bogorienses, 2010)
A green alga, Chlorella vulgaris, was grown semi-continuously at various harvesting periods, and the lipid content and its associated antioxidant activity was examined. The harvesting periods were 9, 18, and 27 days, while the algal culture was placed in 10 L glass bottles provided with aeration for gas exchange and mixing. Light source was obtained from 440 watt cool fluorescent lamps placed at one side of the culture. Room temperature was 26-32C. Algal lipid extraction was done based on liquid phase separation ofmethanol:chloroform:water and the antioxidant activity was examined by means of oxidation inhibitory in ethanol emulsified limnoleic acid. In addition, a TLC analysis was performed to identify the antioxidant compounds soluble in the lipid. The results showed that harvesting period had a significant influence on the algal lipid content, which were 11.94, 12.96, and 16.51% of the dry weight in the culture with harvesting periods of 9, 18, and 27 days, respectively. No remarkable effect of the harvesting period on the antioxidant activity, which were observed to inhibit oxidation of linoleic acid up to 67-71%. There were five compounds found can be associated with the algal antioxidant activity, which were pheophorbide-a, chlorophyll-b, chlorophyll-a, phaeophytin-a, -carotene, and an unidentified one.